Green tea polyphenol epigallocatechin-3-gallate ameliorates insulin resistance in non-alcoholic fatty liver disease mice - Gan Lu; Meng Zi-jun; Xiong Ri-bo; Guo Jin-qiang; Lu Xiao-cui; Zheng Zhi-wei; Deng Yan-ping; Luo Bing-de; Zou Fei; Li Hua (Acta Pharmacologica Sinica, 2017)
Aim: Epigallocatechin-3-gallate (EGCG) is a major polyphenol in green tea. In this study, we investigated the effects of EGCG on insulin resistance and insulin clearance in non-alcoholic fatty liver disease (NAFLD) mice. Methods: Mice were fed on a high-fat diet for 24 weeks. During the last 4 weeks, the mice were injected with EGCG (10, 20 and 40 mg·kg-1·d-1, ip). Glucose tolerance, insulin tolerance and insulin clearance were assessed. After the mice were euthanized, blood samples and tissue specimens were collected. Glucose-stimulated insulin secretion was examined in isolated pancreatic islets. The progression of NAFLD was evaluated histologically and by measuring lipid contents. Insulin-degrading enzyme (IDE) protein expression and enzyme activity were detected using Western blot and immunocapture activity assays, respectively. Results: The high-fat diet significantly increased the body weight and induced grade 2 or 3 liver fatty degeneration (steatosis, lobular inflammation and ballooning) accompanied by severe hyperlipidemia, hyperglycemia, hyperinsulinemia and insulin resistance in the model mice. Administration of EGCG dose-dependently ameliorated the hepatic morphology and function, reduced the body weight, and alleviated hyperlipidemia, hyperglycemia, hyperinsulinemia and insulin resistance in NAFLD mice. Furthermore, EGCG dosedependently enhanced insulin clearance and upregulated IDE protein expression and enzyme activity in the liver of NAFLD mice. Conclusion: EGCG dose-dependently improves insulin resistance in NAFLD mice not only by reducing body weight but also through enhancing the insulin clearance by hepatic IDE. The results suggest that IDE be a potential drug target for the treatment of NAFLD.